Removal of suspended solids, biochemical oxygen demand, ammoniacal nitrogen & nutrients from wastewater - Oon, Yin Wee (Universiti Malaysia Sarawak (UNIMAS), 2005)
This research project focuses on the design, development and performance tests of a two-stage wastewater treatment system, i.e., a trickling filter and water hyacinth-based system operating in series for removal of suspended solids (TSS), ammoniacal-nitrogen (NH;-N), Biochemical Oxygen Demand(BOD) and nutrients, such as nitrogen (N), phosphorous (P), and potassium(K), prior to discharge to natural streams or waterways. The wastewater treatment system consists of two main components operating in series; a) the first stage is a trickling filter filled with perforated cylindrical plastic tubes to provide cross flow alternated with vertical flow; and b) the second stage is the water hyacinth-based system filled with a type of floating local Sarawak water hyacinth (water lettuce). From this applied experimental research, it was found that the removal efficiencies of BOD, NH;-N, N, P, K and suspended solids from wastewaters for 1) trickling filter were approximately 31.9%, 59.9%, 51.6%, 14.7%, 20.1%, and 24.4%, respectively; and 2) water hyacinth-based system were approximately 21.9%, 30.3%, 40.9%, 42.2%, 53.2%, and 29.7%, respectively. The overall removal efficiencies of trickling filter and hyacinth system operating in series were approximately 53.9%, 90.2%, 92.5%, 56.9%, 73.3%, and 54.1%, respectively.